2013
DOI: 10.1038/ng.2794
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the phenotypic effects in the general population of rare variants in genes for a dominant Mendelian form of diabetes

Abstract: Genome sequencing can identify individuals in the general population who harbor rare coding variants in genes for Mendelian disorders1–7 – and who consequently may have increased disease risk. However, previous studies of rare variants in phenotypically extreme individuals have ascertainment bias and may demonstrate inflated effect size estimates8–12. We sequenced seven genes for maturity-onset diabetes of the young (MODY)13 in well-phenotyped population samples14,15 (n=4,003). Rare variants were filtered acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
124
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(132 citation statements)
references
References 84 publications
7
124
0
1
Order By: Relevance
“…audiometry for deafness genotypes). However in support of the general significance of our findings, markedly reduced penetrance estimates have been shown for Mendelian forms of diabetes when taken from population samples (13), and the ClinGen study identified an initial set of variants annotated as pathogenic in OMIM (220 of ~25,000 entries) but now thought to be benign or of uncertain significance (14). In the ClinSeq cohort, with an older age of ascertainment, 45 of 73 individuals with rare heterozygous LOF in a gene that had been reported to cause disease via dominant LOF alleles did not have the expected phenotype (15).…”
supporting
confidence: 68%
“…audiometry for deafness genotypes). However in support of the general significance of our findings, markedly reduced penetrance estimates have been shown for Mendelian forms of diabetes when taken from population samples (13), and the ClinGen study identified an initial set of variants annotated as pathogenic in OMIM (220 of ~25,000 entries) but now thought to be benign or of uncertain significance (14). In the ClinSeq cohort, with an older age of ascertainment, 45 of 73 individuals with rare heterozygous LOF in a gene that had been reported to cause disease via dominant LOF alleles did not have the expected phenotype (15).…”
supporting
confidence: 68%
“…Rare variants in MODY genes previously reported as causal have been identified in normoglycaemic individuals and are therefore likely to be benign variants that do not cause monogenic diabetes [14]. This highlights the limitations of disease variant databases and the need for caution in interpreting published MODY-causing variants.…”
Section: Diagnosing Mody Based On Population Screening: Clinical Revimentioning
confidence: 91%
“…We further hypothesized that the effect of these variants on type 2 diabetes risk in the general population might in some cases be less severe than that estimated in individuals ascertained based on syndromic lipodystrophy (7). To evaluate this hypothesis we sequenced PPARG in 19,752 multiethnic T2D cases/control samples, characterized each nonsynonymous variant through parallel bioinformatic and experimental approaches, and compared the T2D risk of individuals carrying benign and LOF variants.…”
mentioning
confidence: 99%